Lab Study on the Effect of Cation Exchange Capacity on Slurry Performance in Slurry Shields. (3rd October 2018) - Sun, By Pinghe; Zhao, Binkui; Cao, Han; Wang, Jingyuan; Mo, Dingqiang; Zhang, Shaohe
Abstract : Ion stabilizers can enhance the reinforcement slurry effect on the wall and stabilize the wall actively in slurry shields. This paper presents different cation exchange capacities obtained by changing the content of the ion stabilizer (1.5%, 2.0%, 2.5%, 3.0%, 3.5%, 4.0%, 4.5%, 5.0%, 5.5%, and 6.0%) in slurry associated with the basis of the existing slurry formula through the laboratory tests. In order to study the effect of the cation exchange capacity on the performance of slurry properties, the rheological properties of the slurry are analyzed and evaluated by the power law model. Results indicate that the cation exchange capacity of the slurry decreases first and then increases with the increase of the ion stabilizer content. When the content of the ion stabilizer is maintained at 3.50%, the cation exchange capacity reaches the minimum value of 2.92. The filtration volumes, pH values, and rheological parameters of the slurry also indicate an obvious linear change with the change of the cation exchange capacity. The minimum filtration volume is 9.70 mL/30 min when the ion stabilizer content reaches 3.50%. However, the pH value reaches the maximum, that is, 11.34 which is changed from 10, and the change could be considered as a constant value in the field work. When the cation exchange capacity increases, the continuity of polymer structure in the slurry decreases first and then increases, the flow index and consistency coefficient are located within a reasonable range, and the rheological properties of the slurry meet the design requirements of the standards.